Maverick of the Frontier: Commander Henry Leavenworth - Cox, Joshua (My University, 2016)
The purpose of this study is to prove that Henry Leavenworth’s highly interpersonal and innovative leadership style clearly distinguished him as one of the most accomplished commanders of the Early American West.
Keywords: Henry Leavenworth; Arikara War; Arikara Indians; William Ashley; Fort Leavenworth; Fort Gibson